Sensory descriptors, hedonic perception and consumer’s attitudes to Sangiovese red wine deriving from organically and conventionally grown grapes - Pagliarini, Ella; Laureati, Monica; Gaeta, Davide (Frontiers in Psychology, 2013)
In recent years, produce obtained from organic farming methods (i.e. a system that minimizes pollution and avoids the use of synthetic fertilizers and pesticides) has rapidly increased in developed countries. This may be explained by the fact that organic food meets the standard requirements for quality and healthiness. Among organic products, wine has greatly attracted the interest of the consumers. In the present study, trained assessors and regular wine consumers were respectively required to identify the sensory properties (e.g. odor, taste, flavor and mouthfeel sensations) and to evaluate the hedonic dimension of red wines deriving from organically and conventionally grown grapes. Results showed differences related mainly to taste (sour and bitter) and mouthfeel (astringent) sensations, with odor and flavor playing a minor role. However, these differences did not influence liking, as organic and conventional wines were hedonically comparable. Interestingly, 61% of respondents would be willing to pay more for organically produced wines, which suggests that environmentally sustainable practices related to wine quality have good market prospects.